2017
DOI: 10.1038/ncomms14273
|View full text |Cite
|
Sign up to set email alerts
|

A defined syphilis vaccine candidate inhibits dissemination of Treponema pallidum subspecies pallidum

Abstract: Syphilis is a prominent disease in low- and middle-income countries, and a re-emerging public health threat in high-income countries. Syphilis elimination will require development of an effective vaccine that has thus far remained elusive. Here we assess the vaccine potential of Tp0751, a vascular adhesin from the causative agent of syphilis, Treponema pallidum subsp. pallidum. Tp0751-immunized animals exhibit a significantly reduced bacterial organ burden upon T. pallidum challenge compared with unimmunized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 54 publications
(62 reference statements)
2
62
0
Order By: Relevance
“…However, research on virulence determinants of T. pallidum , and our understanding of protective immunity against it, have been hindered by our inability to culture the bacteria in vitro. To overcome this limitation, genome sequencing of T. pallidum directly from clinical samples is now possible 92,238 This advance should enable understanding of strain variation on a global scale, and help to identify outer membrane proteins and other surface antigens as possible vaccine candidates 81 . A recent study showed that immunization of rabbits with the lipoprotein TP071 prevented dissemination of T. pallidum and, hence, has become a promising vaccine candidate 81 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, research on virulence determinants of T. pallidum , and our understanding of protective immunity against it, have been hindered by our inability to culture the bacteria in vitro. To overcome this limitation, genome sequencing of T. pallidum directly from clinical samples is now possible 92,238 This advance should enable understanding of strain variation on a global scale, and help to identify outer membrane proteins and other surface antigens as possible vaccine candidates 81 . A recent study showed that immunization of rabbits with the lipoprotein TP071 prevented dissemination of T. pallidum and, hence, has become a promising vaccine candidate 81 .…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this limitation, genome sequencing of T. pallidum directly from clinical samples is now possible 92,238 This advance should enable understanding of strain variation on a global scale, and help to identify outer membrane proteins and other surface antigens as possible vaccine candidates 81 . A recent study showed that immunization of rabbits with the lipoprotein TP071 prevented dissemination of T. pallidum and, hence, has become a promising vaccine candidate 81 . Integration of potential vaccine targets with diagnostic targets in discovery programmes also hold promise in accelerating progress towards improved tools for control, prevention and ultimately the elimination of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has also been used in the vaccine and bacterial resistance fields. For example, Lithgow Karen et al utilized real‐time PCR to detect the quantity of T. pallidum in New Zealand rabbits, and this method provided the precise immune effect of recombinational proteins Tp0751 and FlaB3. Although T. pallidum has been sensitive to penicillin since it first appeared, we should continue to be vigilant at drug‐resistant strains because of antibiotic abuse and gene mutations.…”
Section: Discussion and Prospectsmentioning
confidence: 99%